Effect of Molasses Addition on the Physical and Nutritional Quality of Silage of Leftover Feed Pennisetum purpureum - Akbar, Mishbahul (Livestock and Animal Research, 2025)
Purpose: Conventional feed management on smallholder farms results in waste of uneaten forage. The leftover feed contains nutrients that can still be used if processed properly. To reduce the waste of leftover feed forage (Pennisetum purpureum), silage feed processing technology, so that it is expected to increase its quality value and reuse.Research Method: The research, silage was made with the following treatments: (T0) used Pennisetum purpureum + molasses 3 %, (T1), (T2) and (T3) used leftover feed of Pennisetum purpureum + molasses with different levels of 3 %, 6 % and 9 %. The results were evaluated by physical assessment, pH, temperature, nutrient content and fleigh value.Findings: The addition of 9% molasses to leftover feed Pennisetum purpureum silage has the best quality in terms of physical, pH, temperature, nutrient content and fleigh point.Research Limitations: The addition of 9 % molasses to the leftover feed silage has the best quality which is close to the results of the control treatment.Originality/ Value:  Research on silage from leftover feed forage is still rare. This research provides information related to the potential reuse of leftover feed forage.